Cluster Analysis of Factors Affecting the Amount of Shipping Costs PT. Indah Logistik Cargo Lampung Branch Using Average Linkage Method - Herindri, Bernadhita; Yoka, Ranara Athlla; Sawitri, Riza (UIN Sumatera Utara, 2024)
Cluster analysis analyzes similar elements as different and independent cluster research objects (not interconnected). PT. Indah Logistik Cargo is a company that provides goods and motorcycle shipping services through three channels: land, sea, and air. This research has three objectives. The first is to categorize postage prices based on the type of goods and services provided so that customers can easily see the options available and understand the differences between each option. Thirdly, categorize prices so companies can offer special promotions or discounts for certain services. Fourth, cluster prices so companies can offer special promotions or discounts for certain services. Based on the analysis results, 3 cluster groups were formed: cheap, medium, and expensive. It can be concluded that the group with low postage prices (Rp 16,160 to Rp 622,160) consists of Medan, Bengkulu, Palembang, Padang, and Pekanbaru; the group with medium postage prices (Rp 40,400 to Rp 888,800) is only Banda Aceh; and the group with high postage prices (Rp 62,620 to Rp 1,555,400) consists of Tanjung Pinang and Pangkal Pinang.